Compound Words in The Land of Stories The Wishing Spell Novel By Chris Colfer - I Gusti Bagus Wahyu Nugraha Putra; Putu Devi Maharani; Kadek Indiani Swari (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2022)
This research mainly aims at finding out the types and describing the meaning of compound words found in the novel The Land of Stories The Wishing Spell by Chris Colfer. This novel consists of 438 pages with 24 chapters. Descriptive qualitative method was used in this research to analyze the data. This research used the theory from McCarthy (2002) and Ullman (1972). The result of this research shows there are three types of compound words found, namely; compound noun, compound adjective, and compound verb with 106 total data found. Meanwhile, there are two kinds of meaning found, those are transparent and opaque meaning.